2021
DOI: 10.1111/geb.13313
|View full text |Cite
|
Sign up to set email alerts
|

Linking phylogenetic niche conservatism to soil archaeal biogeography, community assembly and species coexistence

Abstract: Aim A predictive understanding of the mechanisms underlying microbial biogeographical patterns is of great interest, particularly with respect to phylogenetic distributions of their ecological adaptations. Here, we test whether phylogenetic information can predict the biogeographical distributions, community assembly and species co‐occurrence of soil archaea. Location Northern China. Time period July and August 2017. Major taxa studied Archaeal communities. Methods By conducting a large‐scale (transect interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…There is modeling and empirical evidence that multiple ecosystem functional and structural characteristics undergo abrupt discontinuous transitions and follow a series of sequential ecological thresholds in relation to increases in aridity ( 15 , 20 , 38 ). For instance, MAP causes a rapid shift in the diversity and structure of soil microbes, which would trigger changes in microbial interactions and assembly processes ( 39 ). However, few large-scale studies have quantified whether biogeography distribution and ecological assembly of abundant and rare soil bacteria exhibit abrupt changes to increases in aridity in dryland ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is modeling and empirical evidence that multiple ecosystem functional and structural characteristics undergo abrupt discontinuous transitions and follow a series of sequential ecological thresholds in relation to increases in aridity ( 15 , 20 , 38 ). For instance, MAP causes a rapid shift in the diversity and structure of soil microbes, which would trigger changes in microbial interactions and assembly processes ( 39 ). However, few large-scale studies have quantified whether biogeography distribution and ecological assembly of abundant and rare soil bacteria exhibit abrupt changes to increases in aridity in dryland ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in a variety of ecosystems (e.g., terrestrial and aquatic) support our findings ( 10 , 49 , 50 ). Those studies have suggested that ecological preferences in evolutionary history determined traits and speciation ( 31 , 39 , 51 ). Evolutionary preferences for salinity ( 52 ), high temperature ( 53 ), and substrate ( 54 ) also supported this insight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we assumed that the number of isolated SPs considered could alter biogeographic patterns ( Lennon and Jones, 2011 ; Kramer-Schadt et al, 2013 ). According to our results ( Figure 3 ), successional and spatial factors drove the most apparent biogeographic patterns under the number of three SPs at the taxonomic facet, highlighting the considerable heterogeneity of archaeal assemblage composition suffering from microhabitat changes ( Jiao et al, 2019 , 2021 ). In contrast, at the phylogenetic facet, five SPs were the turning point where the slope of spatial factors began to decrease ( Figure 3 ), and it also indicated the tipping point where the influences of community homogeneity began to emerge, which was mostly contributed by the widely distributed Nitrososphaeraceae ( Figure 4A ).…”
Section: Discussionmentioning
confidence: 67%
“…In addition, soil bacterial abundance varies according to carbon input, temperature, soil depth, and hydration status [ 11 ]. The abundance of microorganisms varies depending upon whether they belong to agricultural and forest soil, wetlands, grass, and desert soils [ 12 ]. Apart from that, sewage as an indicator of the human microbiome can be used broadly to obtain an idea of the microbiome of humans residing in a particular area [ 13 , 14 , 15 ].…”
Section: Diversity Of Microbes In the Environment And Human Bodymentioning
confidence: 99%